PENERAPAN MODEL PBL BERBANTUAN MEDIA DIORAMA\ KEBUTUHAN UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV DI SD 2 SINGOCANDI - Fadya Ndorotul Ainy; Erik Aditia Ismaya; Rani Setiawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the results of learning science using a problem-based learning model assisted by a diorama of class IV needs, chapter 6, how to get all our needs, material me and my needs. Learning outcomes are changes in behavior and overall abilities possessed by students after learning, in the form of cognitive, affective, and psychomotor abilities. Problem-based learning is a learning model that prioritizes how active students are in always thinking critically and always skilled when faced with solving a problem. The action hypothesis in this study is an increase in the results of learning science of class IV students of SD 2 Singocandi. This classroom action research was conducted in class IV of SD 2 Singocandi with 34 students as research subjects. This study lasted for two cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. The independent variable is the problem-based learning model, while the dependent variable is learning outcomes. The instruments of this study were observation, interviews, and documentation. The data analysis techniques used were qualitative and quantitative data analysis techniques.